Morphology of the terminal segments of Megaselia scalaris (Loew)(Diptera: Phoridae) using scanning electron microscopy - Raja Muhammad Zuha Raja Kamal Bashah,; Atiah Ayunni Abdul Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Megaselia scalaris (Loew) (Diptera: Phoridae) is a cosmopolitan scuttle fly of medical and forensic importance. This species is generally small, humpbacked and is a prominent decomposer of corpses indoors. Taxonomically, adult sexes can be distinguished based on the characteristics of the terminal segments of the abdomen. In this report, the terminalia of adult male and female M. scalaris were examined using scanning electron microscope (SEM). The terminal segment of an adult female is less complex compared to male, consisting of an ovipositor and cerci. In male, the hypopygium consists of epandrium, hypandrium, anal tube and penis complex. A pair of long and feathered setae was attached to the tip of the anal tube and tapered. The application of SEM to identify this species isuseful and can be expanded to other species in this fly group.